1993
DOI: 10.1152/ajprenal.1993.265.4.f530
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bone carbonate content in response to metabolic, but not respiratory, acidosis

Abstract: In vitro cultured neonatal mouse calvariae release calcium and buffer the medium proton concentration in response to a decrease in the medium pH caused by a reduction in bicarbonate concentration ([HCO3-]), a model of metabolic acidosis, but not to an equivalent decrease in pH caused by an increase in the partial pressure of carbon dioxide (PCO2), a model of respiratory acidosis. We have postulated that the medium is in equilibrium with the carbonated apatite in bone. To determine whether bone carbonate is dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…Previous in vitro and in vivo studies (62)(63)(64) showed that even in the absence of PTH, metabolic acidosis increases calcium efflux from bone. Moreover, Fraley and Adler (65) showed that the administration of PTH to parathyroidectomized animals that received an acid load increased survival; therefore, the results of these studies suggest not only that in acute metabolic acidosis calcium release from bone is increased independent of PTH but also that PTH acts to enhance calcium release further from bone and to increase buffering capacity.…”
Section: Basal Pthmentioning
confidence: 99%
“…Previous in vitro and in vivo studies (62)(63)(64) showed that even in the absence of PTH, metabolic acidosis increases calcium efflux from bone. Moreover, Fraley and Adler (65) showed that the administration of PTH to parathyroidectomized animals that received an acid load increased survival; therefore, the results of these studies suggest not only that in acute metabolic acidosis calcium release from bone is increased independent of PTH but also that PTH acts to enhance calcium release further from bone and to increase buffering capacity.…”
Section: Basal Pthmentioning
confidence: 99%
“…During models of metabolic acidosis, there is marked calcium efflux from cultured bone, depletion of bone carbonate, stimulation of osteoclastic resorption, inhibition of osteoblastic formation, and a decrease in the formation of mineralized bone nodules (5-7, 13, 14, 17, 20-25, 27-29, 31, 36, 38, 46, 47). However, isohydric respiratory acidosis causes far less calcium efflux, does not appear to affect bone carbonate or osteoblastic or osteoclastic function, and has far less effect on the formation and mineralization of bone nodules (6,7,11,22,27,28,31,70).…”
Section: Discussionmentioning
confidence: 99%
“…The additional protons present in the medium during metabolic acidosis are buffered by the bone mineral whereas there is little buffering of protons during respiratory acidosis (5,6,18,21). The proton buffering during metabolic acidosis is apparently due, at least in part, to the depletion of bone carbonate that occurs during metabolic, but not respiratory, acidosis (22,23).During longer term incubations, there is a significant cell-mediated component of calcium efflux from bone during models of metabolic, but not respiratory, acidosis (7,11,47). Although we have shown that metabolic acidosis increases the resorptive activity of…”
mentioning
confidence: 99%
See 2 more Smart Citations